Implementation of Islamic Religious Education in Cultivating Noble Character of Students at Man 3 Langkat - Ilham, Aulia Maharani; Lubis, Sakban (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2025)
This study aims to produce a description of the implementation of islamic religious education in fostering students morals at MAN 3 Langkat, to find out the morals of students at MAN 3 Langkat and it is expected to overcome poor morals in the school environment, and to find out obstacles in the implementation of moral formation at MAN 3 Langkat. The method used is quakitative with a descriptive analysis approach, by interviewing three reseach informants, namely the principal, islamic religious education teachers and students. The result of this study indicate that students must behave well through the basis of islamic religious education because it can be one of their main capital to form their morals, especially at MAN 3 Langkat, besides students studying, the school also holds extracurriculer activites such as KKD which includes tahfidz, khatib sermons especially for men, Saturday dhikr together from these activities is expected to increase students religious values and form good student mprals.